A comparative study of the efficiency of conventional and Sharia insurance in Indonesia - Ulansari, Dewi Rekno; Septiarini, Dina Fitrisia (Jurnal Keuangan dan Perbankan, 2020)
This study aimed to analyze the value of efficiency and the comparison of efficiency ratio in conventional insurance companies and Islamic Sharia Business Unit (ISBU) of Sharia insurance, both life and general insurance, in Indonesia from 2011-2018. The input variables used are total capital and total expenses. While the output variables in this study were total income. The method used to obtain efficiency value for each insurance industry was Stochastic Frontier Analysis (SFA). The result of efficiency value from the conventional insurance companies and ISBU Sharia insurance would be compared by using independent sample t-test statistic tests. The population in this research was all conventional insurance companies, both life and general, and all life and general insurance of ISBU Sharia insurance that registered in the web of Financial Services Authority (FSA). The sample used was 28 conventional insurance companies consisting of 21 life insurance companies and seven general insurance companies, and 12 ISBU Sharia insurance consisting of nine Sharia life insurance and three Sharia general insurance. This research resulted that there was no difference in efficiency value between conventional insurance companies and ISBU Sharia insurance.JEL Classification: C73, G22, L15Â How to Cite:Ulansari, D. R., Septiarini, D. F. (2020). A comparative study of the efficiency of conventional and Sharia insurance in Indonesia. Jurnal Keuangan dan Perbankan, 24(2), 202-213.DOI:Â https://doi.org/10.26905/jkdp.v24i2.3165